Ambipolar MoS2 Field‐Effect Transistor by Spatially Controlled Chemical Doping. Issue 9 (2nd June 2019) - Liu, Xiaochi; Yuan, Yahua; Qu, Deshun; Sun, Jian
Abstract : Molybdenum disulfide (MoS2 ) is a widely studied 2D semiconductor, which intrinsically exhibits n‐type transport even using the high work function elemental metals as contacts. It is technically challenging to achieve ambipolar field‐effect transistors with MoS2 . Herein, an effective method to prepare p‐doped MoS2 using gold chloride (AuCl3 ) solution is demonstrated. The doping strength can be controlled well by the process parameters. The AuCl3 doping can also be spatially selected using hexagonal‐boron nitride (h‐BN) capping masks. Subsequently, ambipolar transport can be realized in MoS2 with the coexisting parallel n‐type and p‐type channels. The resulting ambipolar MoS2 transistor presents a high room‐temperature performance, showing a high on/off ratio of 10 7 and a mobility of 10 s cm 2 V −1 s −1 for both electron and hole. Abstract : An effective method to prepare p‐doped MoS2 using gold chloride solution is demonstrated. The doping strength can be controlled well by the process parameters. The AuCl3 doping can be spatially selected using hexagonal‐boron nitride (h‐BN) capping masks. Subsequently, ambipolar transport can be realized in MoS2 with the coexisting parallel n‐type and p‐type channels.